Seasonally Resolved Proxy Data From the Antarctic Peninsula Support a Heterogeneous Middle Eocene Southern Ocean. Issue 5 (15th May 2019) - Judd, Emily J.; Ivany, Linda C.; DeConto, Robert M.; Halberstadt, Anna Ruth W.; Miklus, Nicole M.; Junium, Christopher K.; Uveges, Benjamin T.
Abstract: Understanding conditions at both global and local scales during the greenhouse climate of the Eocene Epoch is critical for making accurate predictions in our rapidly warming world. Despite the wealth of proxy data and modeling studies, fundamental aspects of the climate system still remain uncertain. For example, accurate austral high‐latitude temperatures are necessary to understand the evolution of temperatures during the lead‐up to Antarctic glaciation and determine the meridional temperature gradient during greenhouse warmth, yet records are few and disparate. Here we present seasonally resolved temperature and precipitation data from the latest Lutetian ( 42 Ma) from the eastern Antarctic Peninsula. Oxygen isotopes from bivalves indicate a mean temperature of 13.1 °C and a seasonal range of 8.0 °C, slightly (<1 °C) more seasonal than modeled temperatures from high‐obliquity simulations. Carbon isotopes from driftwood suggest that summer accounts for just over half of annual precipitation. When compared with other austral high‐latitude records, the data are consistent with a zonally heterogeneous middle Eocene Southern Ocean. Similar longitudinal variability is observed in the modern boreal high latitudes, where landmasses subdivide the ocean, subjecting basins to their own distinct circulation patterns and coastal processes. With closed Drake and Tasman passages, the middle Eocene Southern Ocean would also have been noncontiguous, resulting in larger variability of sea surface temperatures along individual zonal bands than today. This interpretation resolves inconsistencies among existing high‐austral proxy records and suggests that the large seasonal range of temperatures may be indicative of regional‐scale circulation patterns along the peninsula not captured by low‐resolution climate simulations. Key Points: Middle Eocene coastal waters off the NE Antarctic Peninsula were warm and seasonal, with an equable summer and winter precipitation regime Climate models underestimate the seasonal range indicating unique coastal circulation patterns similar to modern coastal Argentina ( 40°S) Sea surface temperature deviations from zonal means are expected in noncontiguous ocean basins, such as the middle Eocene Southern Ocean